Bioaccumulation and Health Risk Assessments of Heavy Metals in Mussels Collected from Madura Strait, Indonesia - Defri Yona; Aida Sartimbul; Muhammad Arif Rahman; Syarifah Hikmah Julinda Sari; Priyanka Mondal; Abdullah Hamid; Tsania Humairoh (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
HighlightHeavy metals (Cu, Zn, Pb, and Cd) in the seawater, sediment, and soft part of marine mussels were analyzedBioaccumulation Factor (BAF), Estimated Daily Intake and Target Hazard Quotient (THQ) were calculatedHeavy metals in the seawater, sediment and marine mussels were found in varying concentrationsHealth risk assessment indexes showed low values which means insignificant health hazardAbstractMarine mussels are known as one of the biological indicators of heavy metals pollution in the aquatic environment and the sources of protein for human consumption. This study aimed to investigate the concentration of heavy metals (Cu, Zn, Pb, and Cd) in the seawater, sediment, and soft parts of the marine mussels (Perna viridis, Meretrix sp., and Anadara granosa), as well as to evaluate its health risk of consumption from Madura Strait, Indonesia. The seawater, sediment, and marine mussels were obtained from four sites and heavy metal concentrations were analyzed using Atomic Absorption Spectroscopy. In the seawater, heavy metals were in the order of Cu, Pb, Cd, and Zn from the highest to the lowest concentration respectively, while they went down in the order of Zn, Cu, Pb, and Cd in the sediment respectively. Excluding the Pb, higher Cu and Zn concentrations were observed in marine mussels than in seawater and sediments (BAF> 1). Furthermore, it was proven that Cu and Zn were considered as essential metals and required for metabolism, while Pb and Cd were non-essential metals which their biological functions were unknown. The Estimated Daily Intake (EDI) of the marine mussels was lower than the oral reference dose (ORD) and low values of target hazard quotient (THQ < 1) had shown that the consumption of mussels containing heavy metals would not cause significant health risks to humans. The health risk assessment indexes showed low values, which meant insignificant health hazard. However, long-term exposure and the impact of consuming mussels containing heavy metals may require additional investigation